PENGARUH MODEL PAIRED STORYTELLING TERHADAP KETERAMPILAN BERCERITA PADA MATA PELAJARAN BAHASA INDONESIA SISWA SEKOLAH DASAR - Rusyda, Siti Hadaina; Sanusi, Ja'far (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
This study aims to determine the influence of the Paired Storytelling model on storytelling skills in Indonesian subjects of grade IV students of MI Dayatussalam Cileungsi Bogor. This study used quasi-experimental quantitative methods with a population of 62 students consisting of experimental classes and control classes. The data collection techniques used are interviews, observations, and tests. Based on the results of the Independent Samples Test table data, the output of the t test results, obtained the sig value (2-tailed) is 0.010, which means it is smaller than a 0.05 while based on tcalculated t value of 2,644 and ttable t value of 2,000, tcalculated t value is greater than ttable t value. Thus Ho was rejected and Ha accepted, meaning that there was an influence of the paired storytelling model on storytelling skills in subjects Indonesian grade IV students of MI Dayatussalam Cileungsi Bogor.